Comparison of H-mode plasmas in JET-ILW and JET-C with and without nitrogen seeding. (16th March 2016) - Jaervinen, A.E.; Giroud, C.; Groth, M.; Belo, P.; Brezinsek, S.; Beurskens, M.; Corrigan, G.; Devaux, S.; Drewelow, P.; Harting, D.; Huber, A.; Jachmich, S.; et al.
Abstract: In high confinement mode, highly shaped plasmas with edge localized modes in JET, and for heating power of 15–17 MW, the edge fluid code EDGE2D-EIRENE predicts transition to detachment assisted by nitrogen at the low field side (LFS) target when more than 50% of the power crossing the separatrix between ELMs is radiated in the divertor chamber, i.e. ~4 MW. This is observed both in the ITER-like wall (JET-ILW) and in the carbon wall (JET-C) configurations and is consistent with experimental observations within their uncertainty. In these conditions, peak heat fluxes below 1 MW m −2 are measured at the LFS target and predicted for both wall configurations. When the JET-C configuration is replaced with the JET-ILW, a factor of two reduction in the divertor radiated power and 25–50% increase in the peak and total power deposited to the LFS divertor plate is predicted by EDGE2D-EIRENE for unseeded plasmas similar to experimental observations. At the detachment threshold, EDGE2D-EIRENE shows that nitrogen radiates more than 80% of the total divertor radiation in JET-ILW with beryllium contributing less than a few %. With JET-C, nitrogen radiates more than 70% with carbon providing less than 20% of the total radiation. Therefore, the lower intrinsic divertor radiation with JET-ILW is compensated by stronger nitrogen radiation contribution in simulations leading to detachment at similar total divertor radiation fractions. 20–100% higher deuterium molecular fraction in the divertor recycling fluxes is predicted with light JET-C materials when compared to heavy tungsten. EDGE2D-EIRENE simulations indicate that the stronger molecular contribution can reduce the divertor peak power deposition in high recycling conditions by 10–20% due to enhanced power dissipation by molecular interaction.